2023
DOI: 10.1007/s10787-023-01189-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of umbilical mesenchymal stem cell-derived exosomes on CD4+ T cells in patients with primary Sjögren's syndrome

Abstract: Background Primary Sjögren's syndrome (pSS) is an autoimmune disease that leads to the destruction of exocrine glands and multisystem lesions. Abnormal proliferation, apoptosis, and differentiation of CD4+ T cells are key factors in the pathogenesis of pSS. Autophagy is one of the important mechanisms to maintain immune homeostasis and function of CD4+ T cells. Human umbilical cord mesenchymal stem cell-derived exosomes (UCMSC-Exos) may simulate the immunoregulation of MSCs while avoiding the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The occurrence of disease is promoted due to an imbalance between the number of Treg cells and the number of Th17 cells when compared to the healthy control. Other studies have also found that ( 54 ) human umbilical cord mesenchymal stem cell-derived exosomes can inhibit abnormal proliferation of CD4 + T cells and their apoptosis. They can also regulate the balance of Th17 and Treg cell numbers, suppress the secretion of pro-inflammatory factors like IFN-γ, TNF-α, IL-6, IL-17A, as well as IL-17F from CD4 + T cells and induce the secretion of anti-inflammatory factors like IL-10 and TGF-β.…”
Section: Exos and Sjogren’s Syndrome (Ss)mentioning
confidence: 88%
“…The occurrence of disease is promoted due to an imbalance between the number of Treg cells and the number of Th17 cells when compared to the healthy control. Other studies have also found that ( 54 ) human umbilical cord mesenchymal stem cell-derived exosomes can inhibit abnormal proliferation of CD4 + T cells and their apoptosis. They can also regulate the balance of Th17 and Treg cell numbers, suppress the secretion of pro-inflammatory factors like IFN-γ, TNF-α, IL-6, IL-17A, as well as IL-17F from CD4 + T cells and induce the secretion of anti-inflammatory factors like IL-10 and TGF-β.…”
Section: Exos and Sjogren’s Syndrome (Ss)mentioning
confidence: 88%
“…Post-enrichment, the cells were processed through centrifugation over a non-continuous Percoll gradient, specifically layering a 40% Percoll solution atop an 80% solution and centrifuging at 320 g for 25 min. The purified cells were then propagated in RPMI 1640 medium, enriched with 10% FBS, 1% antibiotics, 10 mM HEPES, 2 mM L-glutamine, 1 mM sodium pyruvate, MEM non-essential amino acids, and 55 μM β-mercaptoethanol [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Here we present 3D culture of umbilical cord-derived SCs, mainly UCMSCs and umbilical cord blood MSCs (UCBMSCs). Similar to BMMSC-EVs, EVs derived from 2D cultured UCMSCs have been found to exert protective effects in various ways, such as acute and chronic renal injury, heart injury, liver injury, brain injury, and immunomodulation, as well as alleviation of type 2 diabetes mellitus [ 23 , 173 179 ]. As with BMMSCs, in an in vivo wound healing model, EVs derived from 3D spheroid culture and 3D spinner flask culture of UCMSCs were able to promote epithelialization of wounds and accelerate post-injury skin healing, with a more dramatic effect than 2D-EVs [ 147 , 163 ].…”
Section: Current Applications Of Evs Derived From 3d Cultured Scsmentioning
confidence: 99%